Representation of Gender Equality in Ngeri Ngeri Sedap Films - Larasati*, Auliya Wahyu; Adiyanto, Wiwid (Riwayat: Educational Journal of History and Humanities, 2023)
Film can be the means in deliver issue social the one the story alone contains the problem of gender equality in it, as is the reality of social life equality gender able create distance position between women and men. This study uses a descriptive qualitative method using semiotic analysis from Charles Sanders Pierce. The paradigm in research is clinking to the critical paradigm. This research focuses on signs that show gender equality both verbally and non- verbally on screen on certain scene in the film Horrified Sedap. Theory representation Stuart Hall if be associated with issue equality gender in the film Horrified Horrified will show the film as a medium of criticism today because it is still numerous because it is influenced by reality and culture. The findings on gender equality research are discussed in order to carry out the plan. 2) gender equality in obtaining employment opportunities. 3) the attitude of resistance, the attitude of resistance by the female character against the male character and the resistance of the male character against the male character. 4) the right to voice opinions and concerns of both women and men. 5) the existence of success that has arisen thanks to the cohesiveness of the business of women and men.